Blueberries as a Source of Energy: Physical Chemistry Characterization of Their Anthocyanins as Dye-Sensitized Solar Cells’ Sensitizers - Tatiana Montagni; Mauricio Rodríguez Chialanza; María Fernanda Cerdá (Solar, 2023)
This work aimed to show the possibility of applying anthocyanins extracted from blueberries following a straightforward path as potential impregnation dyes in dye-sensitized solar cells (DSSCs), particularly in the presence of co-adsorbents, such as silver nanoparticles, as an alternative in order to profit from large amounts of discarded fruits. Following a simple procedure, anthocyanins (mainly delphinidin-3-glucoside) were obtained from blueberries (Southern Highbush type). Complete characterization was carried out in order to prove the utility of delphinidin-3-glucoside as a sensitizer in DSSCs. The analyzed anthocyanin is suitable for sensitizing because of its high molar absorptivity values within the visible region of the light spectra, the adsorption ability to a FTO/TiO2 electrode (FTO, fluorine-doped tin oxide) as confirmed by Fourier transform infrared (FTIR) as well as thermogravimetry coupled to differential scanning calorimetry (TG-DSC), a potential oxidation value near 1 V, and adequate thermal as well as light stabilities. Moreover, the cell’s conversion efficiency is improved in the presence of silver nanoparticles, reaching 0.24% (nearly a 25% increase). The sum of all these characteristics points to the application of delphinidin-3-glucoside as a sensitizer in DSSCs, offering a technological use with potential interest for countries where agricultural production offers an abundant origin of extraction.